The Ultilization of Flipgrid Application to Strengthen Students' English Speaking Performance Perspective - Tyas, Novita Kusumaning; Intes, Amina; Barroso, Uwe (Journal International Inspire Education Technology, 2024)
There are four skills that students must achieve in learning English, namely speaking, listening, writing and reading. Making presentations in English is a common thing to do in English classes. The ability to speak in this case is very necessary, but in reality students have limited opportunities to practice English. Flip grid application is one of the applications that can be utilised to improve English speaking skills. This study aims to find students' perspectives on the use of flipgrid application to improve English speaking skills. This research uses descriptive quantitative method. The results of this study can be seen in the responses given by students to the flipgrid application. Students gave good responses to the use of flipgrid in improving pronunciation skills, grammar, vocabulary, practising expressions, as well as the psychological benefits of using flipgrid. The students also showed a very good response to the benefits of the features in the flipgrid application. These features can certainly encourage the improvement of students' English speaking skills. This is also indicated by the excellent response from students to the benefits of flipgrid in improving English speaking skills.